Analysis of The Relationship Between Manual Handling and Individual Factors with De Quervain Syndrome In Workers of Heavy Equipment Manufacturing Company PT. K - Finna Fitriana; Dewi Sumaryani Soemarko; Nuri Purwito Adi; Herqutanto -; Pukovisa Prawiroharjo (ILUNI MKK FKUI and PRODI MKK FKUI, 2024)
Introduction: According to the European Occupational Disease Statistics in 2016, as much as 38.1% of Occupational Diseases are Musculoskeletal Disorders. Research in 2013 on the electrical assembly industry in Thailand showed that the most common cause of upper extremity MDS is De Quervain syndrome (DQS) with a prevalence of 13.03%. Previous studies showed that occupational factors are very important as risk factors for DQS, in addition to individual factors. Caused by excessive use of the muscles around the fingers to the wrist, sustained repetitive movements, forceful manual exertion and prolonged static position. In manufacturing industry, the production process need to use tools, machines, and still requires workers for manual work activities and work processes that cannot be replaced by machines. Because manual handling is one of the occupational risk factors for DQS, it is necessary to study DQS in manufacturing industry. This study aims to determine the prevalence of DQS, identify, and analyze the relationship between manual handling and individual factors related to DQS.Method: This research method is a cross sectional using secondary data of PT K employees’ Medical Check-Up (MCU) in 2021. The samples used was all employee’s MCU data with total of 1244 samples. Independent variables include manual handling work factors and individual factors, include age, gender, and years of service. The dependent variable is the De Quervain Syndrome. The DQS was diagnosed with Finkelstein test.Results: A total of 1244 respondents were obtained, with the DQS prevalence 9%. In the analysis of the relationship between manual handling work factor and individual factors (age, sex, and years of service) showed that no significant relationship with suspected DQS in PT K workers. Whereas the multivariate analysis showed that there were no factors that most dominantly influenced DQS, with p>0.05. Conclusion: There is no significant relationship between manual handling work factor and individual factors on suspected DQS.